Is counting hindering learning? An investigation into children's proficiency with simple addition and their flexibility with mental computation strategies. Issue 1 (2nd January 2022) - Hopkins, Sarah; Russo, James; Siegler, Robert
ABSTRACT: There is a growing awareness that many children are not developing fast and accurate retrieval-based strategies for solving single-digit addition problems. In this study we individually assessed 166 third and fourth grade children to identify a group of children (called accurate-min-counters) who frequently solved simple single-digit addition problems using a min-counting strategy and were accurate using it. We investigated if these children were adaptive when it came to using retrieval for simple addition and if they were disadvantaged when it came to demonstrating mental computational flexibility with multi-digit addition. We found accurate-min-counters represented over 30% of participants. These children were often incorrect when they were required to use retrieval for simple addition and were less flexible than most peers with mental computation strategies. The findings indicate that educators should be concerned about the prevalence of accurate-min-counting and call into question the widely held view that it is mostly children with a mathematics learning disability (or persistent low achievement) who display the protracted use of counting-based strategies for simple addition. Further research is needed to investigate if, and how, current teaching approaches are encouraging children to rely on counting beyond a time when it is advantageous to do so.